Об однозначной разрешимости периодической краевой задачи для системы гиперболических уравнений - Орумбаева, Н.Т.; Сабитбекова, Г. (Изд-во КарГУ, 2011)
Мақалада аралас туындылы гиперболалық теңдеулер жүйесі үшн периодты шеттік есеп қарастырылады. Гиперболалық теңдеулер жүйесі үшін периодты шеттік есептің шешімін табудың конструктивті алгоритмі ұсынылады. Алгоритмнің жинақтылығының жəне зерттелініп отырған есептің шешілімдігінің жеткілікті шарттары тағайындалады. Periodic boundary problem for system of the hyperbolic equations with mixed derivative is considered in the article. The constructional algorithm of finding periodical boundary problem’s solution for system of hyperbolic equations is offered. The necessary and sufficient conditions of algorithm and one-valued solvability of investigating problem are established.
On one-valued solvability of the periodic boundary problem for system of the hyperbolic equations